Quality Analysis Of Nursing Services Towards Internal Disease Inpatient Satisfaction At The Prima Indonesia Royal Hospital During The Covid-19 Pandemic Of 2021 - Andre Jonathan Samuel Gultom; Wienaldi Wienaldi; Maya Sari Mutia; Ali Napiah Nasution (CV. Inara, 2022)
The Covid-19 pandemic has caused a decrease in the number of patient visits and changes in service procedures for patients being treated to prevent transmission of Covid-19. This has an impact on decreasing patient satisfaction with service quality which includes physical evidence, reliability, responsiveness, assurance, and empathy. The purpose of this study was to analyze the quality of nursing services on the satisfaction of internal medicine inpatients during the Covid-19 pandemic. This research is a quantitative analytic study with a crosssectional approach. The research was conducted at the Royal Prima Hospital, Medan. Theresearch population was 285 people, the sample obtained was 166 people. Sampling by purposive sampling. Data analysis was univariate, bivariate with a chi-square test, and multivariate with multiple logistic regression at a 95% confidence level (α = 0.05). The results showed that the quality of nursing services affected the satisfaction of inpatients for internal medicine at the Royal Prima Hospital Medan during the Covid pandemic including physical evidence (p = 0.000), and reliability (p = 0.008), responsiveness (p = 0.001), and assurance. (p=0.000). While the factor that has no effect is empathy (p = 0.959). The physical evidencevariable (tangibles) is the most dominant variable affecting the satisfaction of internal medicine inpatients during the Covid-19 pandemic with a value of Exp(B)/OR = 13,773. Patients who stated good physical evidence had a 13.7 times higher chance of being satisfied than patients who stated poor physical evidence